A wireless crane to vessel locating system for sea swell compensation - Nikolaiev, Anton; Kirsch, Fabian; Vossiek, Martin; Shu, Xinyu; Bohn, Christian; Duden, Heinrich (2014 20th International Conference on Microwaves, Radar and Wireless Communications, MIKON 2014, 2014)
Sea swell causes significant risk in transferring people and material to offshore constructions and oftentimes hamper the accessibility completely. The weather window where a construction is accessible can be enlarged notably if a crane is equipped with a sea swell compensation system. For a crane to vessel swell compensation system it is required to measure the 3D position of the crane load handling device relative to the deck of ship precisely, reliably and in real-time. In this paper a novel wireless crane to vessel locating system is introduced. Several secondary radar units that are mounted on the ship deck are measuring the distance to a responder unit attached to the crane boom. The 3D localization is based on a fusion of secondary radar distance measurements and the data from an inertial sensor platform. The fusion is done by a quaternion based extended Kalman filter which implements both multilateration and strapdown inertial navigation techniques. Real measurement data acquired with the inertial platform on a ship and radar data measured with the realized local positioning radar onshore are fed in a PC based simulation of the complete system. The real data simulations prove that the developed real time locating system provides the required position information precisely and reliably. By this it is shown that the novel wireless locating system is well suited for sea swell compensation equipment.
Keywords: inertial navigation; Kalman filter; Radar position measurement; radio navigation; swell compensation